BOPENS: An Interactive Media To Help Student in Remote Areas During Pandemic - Yuni Hartati Eliya Rosa; Alfatih Mutiasa Praja; Nur Zahwa (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
Decree of the Minister of Education and Culture RI Number 4 of 2020 Regarding the Implementation of Education Policy in Period Emergency Spreading Corona Virus Disease (Covid-19) so that the learning process starts from the level of Paud up to college doing online learning. However, not all students stay in remote areas can take part online learning this is due to limited internet access and electricity. Therefore to help the learning process continues, the authors provide an audio based interactive learning media BOPENS (book e-Pens) pen (e-Pens) on SAINTEK material that can help students understand learning materials at home with facilities complete audio explanation of the material, discussion of practice questions, MP3, and Recording.